The Effect of Functionalization Carbon Nanotubes (CNTs) on the Performance of PES-CNTs Mixed Matrix Membrane - Ahmad Mustafa; Tutuk Djoko Kusworo; Abdullah Busairi; Ahmad Fauzi Ismail (Chemical Engineering Diponegoro University, 2010)
A new type of mixed matrix membrane consisting of functionalized carbon nanotubes (CNTs) and polyethersulfone (PES) is prepared for biogas purification. PES mixed matrix membrane with and without modification of carbon nanotubes were prepared by a dry/wet phase inversion technique using a pneumatically flat sheet membrane casting machine system. The modified carbon nanotubes were prepared by treating the carbon nanotubes with chemical modification using Dynasylan Ameo (DA) silane agent to allow PES chains to be grafted on carbon nanotubes surface. The results from the FESEM, DSC and FTIR analysis confirmed that chemical modification on carbon nanotubes surface had taken place. Meanwhile, the nanogaps in the interface of polymer and carbon nanotubes were appeared in the PES mixed matrix membrane with unmodified of carbon nanotubes. The modified carbon nanotubes mixed matrix membrane increases the mechanical properties, the productivity and purity of biogas. For PES-modified carbon nanotubes mixed matrix membrane the maximum selectivity achieved for CO2/CH4 is 36.78